Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have moment generating function

$$ M_z (t) = \dfrac {\lambda^2} {(\lambda-at) (\lambda-t)}, $$ and I'm trying to calculate the PDF from this function. I feel like some kind of inverse transform is required here, but I can't figure it out.

share|cite|improve this question
Have you considered that this mgf is the product of 2 mgfs? Given $X$ and $Y$ are independent random variables and $W = X+Y$, the mgf of $W$ is $M_W(t) = M_X(t) + M_Y(t)$. I am thinking something like $\frac{\lambda^2}{(\lambda-at)(\lambda-t)}=\begin{pmatrix}\frac{\lambda}{\lambda - at}\end{pmatrix}\begin{pmatrix}\frac{\lambda}{\lambda - t}\end{pmatrix}$ – bryansis2010 Mar 27 '13 at 17:09
Try partial fractions, and then see if you can find what kind of random variable has an MGF of the form $\lambda/(\lambda-at)$ or $\lambda/(\lambda-t)$. – Dilip Sarwate Mar 28 '13 at 3:28
@bryansis2010 If $X$ and $Y$ are not independent, what is the mgf of $W=X+Y$? – Dilip Sarwate Mar 28 '13 at 3:30
@DilipSarwate One assumes that X and Y are independent here... :-) – Did May 2 '13 at 23:59
@bryansis2010 don't you mean $M_w(t) = M_X(t)M_Y(t)$, i.e., the product? See Theorem 4.2.12 in Casella & Berger. – chbrown Oct 29 '13 at 3:42

Inverting generating functions is not always easy. It does help to state any constraints on the parameters (which are left unstated here by the OP). Anyway, the approach is: First, convert your mgf into a characteristic function (i.e. replace t -> I t):

Next, invert the characteristic function to yield the pdf (using Mathematica here), using an inverse fourier transform. To get a 'neat' result, it appears we need the parameter constraints {a > 0, $\lambda$ > 0}, so I have added these as assumptions:

HeavisideTheta[x] is a function that is 0 for x<0, and 1 for x > 0, so our pdf is:

Finally, a quick check to make sure all is OK: generate the mgf from the pdf to see it is the same as that we started with (here using the Expect function in mathStatica/Mathematica):

... and all is OK :)

Finally, here is a quick plot of the derived pdf, as parameter $\lambda$ varies:

PlotDensity[f /. {a -> 2, \[Lambda] -> {2,3,4}}]

share|cite|improve this answer
Why not using directly InverseLaplaceTransform? Is there some inner subtlety of the workings of Mathematica which would make preferable a detour by Fourier? – Did May 3 '13 at 8:27

(This explains in detail a suggestion by @Dilip then expands briefly on another one by @bryanis2010, both leading to excellent general approaches. Thus, the aim of this post is to provide a mathematical answer to a question which has none, so far.)

As every rational function, $M_Z$ can be decomposed into partial fractions, here, for every $a\ne1$, $$ M_Z(t)=\frac{u}{\lambda-at}+\frac{v}{\lambda-t}, $$ for some parameters $u$ and $v$ one can readily identify as $u=-a\lambda/(1-a)$ and $v=\lambda/(1-a)$.

Now, one of the easiest to remember generating functions is that, if $X$ is standard exponential, then $$ M_X(t)=E[\mathrm e^{tX}]=\int_0^{+\infty}\mathrm e^{tx}\mathrm e^{-x}\mathrm dx=\frac1{1-t}. $$ Hence, for every positive $\mu$, $$ \frac1{1-\mu t}=E[\mathrm e^{t\mu X}]. $$ Applying this to $\mu=1/\lambda$ and to $\mu=a/\lambda$ yields $$ M_Z(t)=\frac{u}{\lambda}E[\mathrm e^{taX/\lambda}]+\frac{v}{\lambda}E[\mathrm e^{tX/\lambda}]. $$ This indicates that $$ M_Z(t)=\frac{u}{\lambda}\int_0^{+\infty}\mathrm e^{tax/\lambda}\mathrm e^{-x}\mathrm dx+\frac{v}{\lambda}\int_0^{+\infty}\mathrm e^{tx/\lambda}\mathrm e^{-x}\mathrm dx, $$ that is, $$ \int_0^{+\infty}\mathrm e^{tx}f_Z(x)\mathrm dx=-\frac{a}{1-a}\int_0^{+\infty}\mathrm e^{tx}\mathrm e^{-x\lambda/a}\frac{\lambda}a\mathrm dx+\frac1{1-a}\int_0^{+\infty}\mathrm e^{tx}\mathrm e^{-x\lambda}\lambda\mathrm dx, $$ hence, finally, $$ f_Z(x)=\frac{\lambda}{1-a}(\mathrm e^{-x\lambda}-\mathrm e^{-x\lambda/a}). $$ The simplest method to solve the case $a=1$ might be to consider the limit when $a\to1$ of this expression, yielding the correct gamma density $$ f_Z^{(a=1)}(x)=\lambda^2x\mathrm e^{-x\lambda}. $$

Another method, suggested by @bryanis2010 in comments is to note that $M_Z$ is the product of two generating functions, each easily identifiable, namely $$ M_Z(t)=\frac{\lambda}{\lambda-at}\cdot\frac{\lambda}{\lambda-t}=E[\mathrm e^{atX/\lambda}]\cdot E[\mathrm e^{tX/\lambda}], $$ hence $Z$ is distributed as $(aX+Y)/\lambda$ where $Y$ is also standard exponential, independent from $X$. This yields $f_Z$ as the convolution of two well known densities, for the same end result as above, the $a=1$ case (gamma random variable) being particularly direct.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.